Taller PRACTICE READING y su influencia en la comprensión lectora en los estudiantes de la asignatura de Historia de la Literatura de la lengua inglesa siglo XIX y XX de la Escuela Académico Profesional de Idiomas de la Universidad Nacional de San Martin - Tarapoto 2012 - Jimenez Flores, Juana Josefa (2013)
In the learning process, to understand what it is read turns out to be fundamental, because the person tends to learn, in the most cases, through reading; therefore, the conduction of the teaching learning process should give him/her suitable capacities to understand a written text. The reading comprehension however, is a latent problem, since the students don't know how to understand a minimum of fluency what they read. This research named: PRACTICE READING WORKSHOP ANO ITS INFLUENCE IN THE READING COMPREHENSION IN THE STUDENTS OF HISTORY OF ENGLISH LANGUAGE LITERATURE ASIGNATURE OF XIX ANO XX CENTURY OF THE PROFESIONAL ACADEMIC LANGUAGE SCHOOL OF THE NATIONAL UNIVERSITY OF SAN MARTIN - TARAPOT0-2012 was aimed to measure the influence of PRACTICE READING workshop in the reading comprehension of students in the literal and inferential components. The field data collection was applied at San Martin National University, Faculty of Education and Humanities in the professional academic language school, obtaining as sample 27 students of 7th cycle of History of the English Language Literature nineteenth and twentieth century subject. To measure the students' reading comprehension was applied an exam of pre-test at the beginning and a post-test at the end of the eight pedagogical workshops, based on 40 questions, divided in two components, literal and inferential. As for the results obtained of the research indicate that the PRACTICE READING workshop has significantly influenced in the reading comprehension of the students of History of English Literature nineteenth and twentieth Century subject of the Professional Academic Language School of the San Martín National University - Tarapoto - 2012 , according to the chart Nº 01 which shows a great improvement between the pre-test and post-test. For this reason, in the results of the hypothesis test according to the chart Nº 6 rejects the null hypothesis and accepts the research hypothesis.